Public Relations (PR) as a strategic tool for the transformation and development of higher education at the regional universities of the region - Dzamukashvili, Lali (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
In today's world of increasing competition among academic institutions, the positive image of a university is of particular importance in attracting students, researchers and funding. The effective work of the Public Relations Department (PR) plays a crucial role in the process of supporting the mission and goals of the university; in managing internal and external communication, transparency, balancing institutional, academic interests and adapting to digital communication. The reputation of the university is created and maintained and its formation in the long-term mode is thanks to PR.